Analysis of UV-B regulated miRNAs and their targets in maize leaves - Casati, Paula (2013)
UV-B radiation elicits physiological and developmental changes in plants. In this work, to characterize the mechanisms of gene regulation by UV-B radiation, the global miRNA expression profiles in juvenile maize leaves were compared under control conditions in the absence of UV-B and after an 8 h-UV-B treatment similar to ambient UV-B levels using small RNA microarrays. Seventeen miRNA s were identified that were differentially expressed in response to UV-B. In parallel, the expression of putative mRNA targets was examined in mRNA microarrays using the same RNA samples used for the small RNA analysis. In general, there is a strong negative correlation to the miRNA expression. Thus, post-transcriptional regulation is an important step in gene expression by UV-B radiation in maize.